Proposta de aplicação e monitoramento do plano de gerenciamento de resíduos da Universidade Estadual Paulista (UNESP) Campus Rio Claro/SP - Dolphine, Larissa Marchetti [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The high rate of waste generation is a much-discussed issue nowadays because of its steady growth and the associated environmental and social problems. Thus, applicable laws have been created to regulate this condition, such as the National Solid Waste Policy (NSWP), which covers the important concept of shared responsibility, where every generator is responsible for its waste, and the development and deployment of a Waste Management Plan (WMP), in private or public companies, municipalities, institutions, governments, become essential. The presented project proposes the WMP implementation and monitoring at the UNESP Rio Claro Campus, through the auditing application and proposals of corrective and preventive actions, in order to obtain a continuous waste management improvement, generated by this educational institution. The used methodology was the PDCA, consisted of a continuous improvement cycle method, and this research performed the C (Check) phase. In this methodology, the NSWP was included in the all phases execution, as this legislation corresponds to a management tool, having in its content, important environmental management instruments, such as the Waste Management Plan, covered in this work. In proposed goals and actions elaboration for each waste, another important method was used for waste management, called 4 R's (Reduce, Reuse, Recycle and Rethink). Audits were applied in 48 sectors of Unesp Rio Claro / SP, covering the two Institutes that comprise it: the Institute of Biosciences and the Institute of Geosciences and Exact Sciences. These audits were applied based on the preparation of a checklist based on the PNRS, containing type, quantity, and management information (Segregation, Storage, Treatment, Transport / Final Destination). Three measurement categories were adopted on waste accounting, according to the waste type: kilograms/year; units/year and liters/year. The accounted for waste in higher quantity for each category...

A elevada taxa de geração de resíduos é uma questão muito discutida atualmente, devido ao seu constante crescimento e aos problemas ambientais e sociais associados. Desse modo, surgem legislações aplicáveis, como a Lei 12305/10- Política Nacional de Resíduos Sólidos (PNRS), que abrange o conceito de responsabilidade compartilhada, no qual todo gerador é responsável por seu resíduo, e a elaboração e implantação de um Plano de Gerenciamento de Resíduos (PGR) em empresas privadas e públicas, municípios, instituições e governos tornam-se importantes. Este trabalho propõe a implementação e o monitoramento do PGR na UNESP Campus Rio Claro/SP, através da aplicação de auditorias e propostas de ações corretivas e preventivas, a fim de obter uma melhoria contínua no gerenciamento adequado dos resíduos gerados por essa instituição de ensino. A metodologia utilizada foi o PDCA, sendo um método de ciclo de melhoria contínua, e a etapa realizada nesta pesquisa foi a C (Check). Nessa metodologia, a PNRS foi incluída na execução de todas as fases, uma vez que essa legislação corresponde a uma ferramenta de gestão, apresentando em seu conteúdo, instrumentos de gestão ambiental, como o Plano de Gerenciamento de Resíduos, abordado neste trabalho. Na elaboração das metas e ações propostas para cada resíduo, foi utilizado um outro método importante para o gerenciamento de resíduos, denominado 4 R's (Reduzir, Reutilizar, Reciclar e Repensar). Foram realizadas auditorias em 48 setores da Unesp Rio Claro/SP, abrangendo os dois Institutos que a compõem: o Instituto de Biociências e o Instituto de Geociências e Ciências Exatas. Essas auditorias foram executadas a partir da elaboração de um check list baseado na PNRS, contendo informações de tipo, quantidade e gerenciamento (Segregação, Armazenamento, Tratamento, Transporte/Destinação Final). Na contabilização dos resíduos, foram adotadas três...
Keywords: Política Nacional de Resíduos Sólidos (Brasil); Universidade Estadual Paulista Júlio de Mesquita Filho Instituto de Biociências (Campus de Rio Claro); Universidade Estadual Paulista Júlio de Mesquita Filho Instituto de Geociências e Ciências Exatas; Resíduos; Política ambiental; Gerenciamento de resíduos; Resíduos sólidos; Gestão ambiental; Auditoria ambiental; Rio Claro (SP)